College Of Architecture - (:unkn) unknown (My University, 2018)
The concept of the project is that architecture is a concentrated and intensified state of the products of humans quest to achieve his needs and make them closer to him. In addition to his interaction with the surrounding environment and environment, he created a feeling that led him to a thought related to the factors influencing his life and behavior. Therefore there is constant movement and action. Think and act focused on the design process and create an interactive environment between users through semi-continuous spaces and at the same time increase interaction with the external environment and squares and gradient spaces to increase communication with the surrounding environment as well as give importance to exhibitions and achievements of students and make them going with movement through the building.